2022
DOI: 10.3390/en15155536
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of Renewable Energy Sources in Germany and the Influence of Land Use Datasets

Abstract: Potential analyses identify possible locations for renewable energy installations, such as wind turbines and photovoltaic arrays. The results of previous potential studies for Germany, however, are not consistent due to different assumptions, methods, and datasets being used. For example, different land-use datasets are applied in the literature to identify suitable areas for technologies requiring open land. For the first time, commonly used datasets are compared regarding the area and position of identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…In our study, we use data from Auer et al [69] for the potential of wind and solar. To put these numbers into context, we compare them against results of a meta-analysis on renewable potential in Germany in the appendix D [70]. The material demonstrates that the assumed potential is in line with results of the meta-analysis, except for PV, for which our assumptions are more conservative.…”
Section: Renewable Supplymentioning
confidence: 76%
“…In our study, we use data from Auer et al [69] for the potential of wind and solar. To put these numbers into context, we compare them against results of a meta-analysis on renewable potential in Germany in the appendix D [70]. The material demonstrates that the assumed potential is in line with results of the meta-analysis, except for PV, for which our assumptions are more conservative.…”
Section: Renewable Supplymentioning
confidence: 76%
“…As the GM PV model was not originally designed to assess rooftop PV, we used the 3D building data from ATKIS and calculated the modi ed roof area using the equation from (Risch et al, 2022). We found that 90 ha of rooftops are available for PV expansion (Table 2).…”
Section: Gm Pv Scenariosmentioning
confidence: 99%
“…In this endeavour, photovoltaics (PV), including both ground-mounted PV (GM PV) and rooftop PV systems, play a central role. The goal is to increase the share of renewable energies in gross electricity consumption from 46% in 2022 to 80% by 2030 (Kullmann, 2023;Risch et al, 2022). In 2022, PV accounted for 11% of German electricity generation, with plans to expand its capacity signi cantly.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates a rigorous process for the identification of appropriate sites, commonly referred to as "land eligibility" (LE). A major challenge in this process is the issue of comparability across different assessment tools, surrounded by the absence of standardized data sources [22]. Finally, the optimal land allocation strategy remains unaddressed in ESOMs.…”
Section: Introductionmentioning
confidence: 99%